Modelling brain dopamine-serotonin vesicular transport disease in Caenorhabditis elegans - Alexander T. Young; Kien N. Ly; Callum Wilson; Klaus Lehnert; Russell G. Snell; Suzanne J. Reid; Jessie C. Jacobsen (The Company of Biologists, 2018)
Brain dopamine-serotonin vesicular transport disease is a rare disease caused by autosomal recessive mutations in the SLC18A2 gene, which encodes the VMAT2 protein. VMAT2 is a membrane protein responsible for vesicular transport of monoamines, and its disruption negatively affects neurotransmission. This results in a severe neurodevelopmental disorder affecting motor skills and development, and causes muscular hypotonia. The condition was initially described in a consanguineous Saudi Arabian family with affected siblings homozygous for a P387L mutation. We subsequently found a second mutation in a New Zealand family (homozygous P237H), which was later also identified in an Iraqi family. Pramipexole has been shown to have some therapeutic benefit. Transgenic Caenorhabditis elegans were developed to model the P237H and P387L mutations. Investigations into dopamine- and serotonin-related C. elegans phenotypes, including pharyngeal pumping and grazing, showed that both mutations cause significant impairment of these processes when compared with a non-transgenic N2 strain and a transgenic containing the wild-type human SLC18A2 gene. Preliminary experiments investigating the therapeutic effects of serotonin and pramipexole demonstrated that serotonin could successfully restore the pharyngeal pumping phenotype. These analyses provide further support for the role of these mutations in this disease.